An aortopulmonary tunnel as an extra-cardiac systemic to pulmonary shunt - Ishak, Azril; Abu Hassan, Hasyma; Mohammed, Yusri (Longe Medikal, 2022)
Aortopulmonary window, one of the rarest congenital heart diseases, causes unrestricted left-to-right shunt and may lead to congestive heart failure, pulmonary vascular obstructive disease and low cardiac output. Echocardiogram and CT angiography are important non-invasive diagnostic tools. Surgical closure is indicated in all patients diagnosed with APW and is usually performed at the time of diagnosis to reduce the risk of developing early pulmonary vascular disease. We report on a term baby girl with variant of aortopulmonary window which manifest as a tunnel on CT angiography.